PEMBINAAN SISWA/I SMK WIDYA BATAM TERHADAP PROGRAM KESELAMATAN BERLALU LINTAS DALAM ETIKA BERKENDARA - Anggia Arista; Rahmat Fauzi; Erlin Elisa (ASOSIASI IDEBAHASA KEPRI, 2023)
Technological developments also have an impact on the transportation system on the highway. One of them is the various types and types of transportation used by society today. Based on data, every year 1.3 million people die as a result of road traffic accidents and more than 3,000 people die every day due to traffic accidents. One of the cities in Indonesia that is classified as having the highest traffic accident record, namely Batam. The rate of traffic accidents in Batam City has increased every year, where data states that there has been an increase in traffic accidents of 47% for the 2019-2020 period. The high traffic accidents in Batam generally occur due to a lack of public knowledge and awareness in driving and traffic, especially among school children and adolescent drivers. As happened at SMK Widya Batam, where almost 80% of the students use motorbikes for school transportation. Therefore, through fostering the Traffic Safety program socialization in driving ethics for Widya Batam Vocational School students both within the school environment and outside the school environment, it is hoped that it can provide the transfer of information and knowledge about the importance of increasing awareness of driving ethics and concern for traffic safety and also participate participate in maintaining security, order and safety on the road.